2004
DOI: 10.1007/s10336-004-0030-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of the uropygial gland secretion of Hume’s ground jay Pseudopodoces humilis and its taxonomic implications

Abstract: Hume's ground jay (Pseudopodoces humilis), a species living in the high altitude steppes of the QinghaiTibet-Plateau (China), was traditionally thought to be a ground jay related to the genus Podoces (Corvidae). Recently, however, based on three independent datasets (comparative osteology, nuclear and mitochondrial DNA sequences), this species was discovered to be a member of the Paridae. Here, we reinvestigate the systematic position of Pseudopodoces humilis using the chemical composition of uropygial gland s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…However, chemical composition of the uropygial secretions of birds do not usually included peptides (Burger et al . 2004; Gebauer et al . 2004; Montalti et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, chemical composition of the uropygial secretions of birds do not usually included peptides (Burger et al . 2004; Gebauer et al . 2004; Montalti et al .…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, our experiments might have also deactivated antimicrobial peptides that are directly produced by hoopoes. However, chemical composition of the uropygial secretions of birds do not usually included peptides (Burger et al 2004;Gebauer et al 2004;Montalti et al 2005) and, thus, this explanation is unlikely. In any case, and whatever the origin of deactivated peptides, the association between the experimental effects on bacterial growth and hatching failures detected in hoopoes, at least indicated that protease on the eggshell provoked an increased probability of bacterial infection that might be the cause of the increase in hatching failures.…”
Section: Discussionmentioning
confidence: 99%
“…Except for some recent studies on intact secretions of Charadriformes (Reneerkens et al 2002) and the woodhoopoes (Burger et al 2004), most of the chemical studies were on the hydrolyzed or esterified products of the secretion and very little is known about their intact components (Gamo 1971;Gebauer et al 2004;Jacob and Ziswiler 1982;Morr et al 1992;Odham 1967). They consist mostly of monoesters of saturated, unbranched and or mono methyl, di-methyl and poly methyl branched carboxylic acids.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of preen wax using GC‐MS usually involves hydrolysis of the preen wax components, leading to loss of information concerning the distribution of molecular species (Kolattukudy et al. 1985, 1987, Gebauer et al. 2004).…”
mentioning
confidence: 99%